Tangeretin Suppresses Fumonisin Production by Modulating an NmrA- and HSCARG-like Protein in Fusarium verticillioides - Liuqing Wang; Wenlei Zhai; Dongmei Jiang; Nan Jiang; Jiaqi Yan; Haoyun Jiang; Meng Wang (Journal of Fungi)
Fumonisins are polyketide-derived mycotoxins posing significant health threats to humans and animals. Among these, fumonisin B1 (FB1) is the most prevalent mycotoxin, primarily produced by Fusarium verticillioides, especially in maize and its derived products. Tangeretin, a polymethoxyflavonoid, has been identified as having potential medicinal properties, particularly as an antioxidant. To evaluate the antifungal and anti-mycotoxigenic properties of tangeretin and to elucidate the mechanisms underlying its inhibitory effects, assessments of fungal growth, FB1 production, conidial germination, and cellulase activity, antioxidant capacity and enzyme activities, transcriptomic analysis and gene deletion experiments were conducted. Consequently, tangeretin significantly curtailed fungal growth and FB1 production and provided protection against pathogenic infection on corn. It affected genes associated with fungal growth, conidial development, and antioxidant response. Furthermore, tangeretin interfered with the supply of biosynthetic substrate necessary for fumonisin production, particularly impacting pathways involved in alanine metabolism, pyruvate metabolism, fatty acid degradation, and sphingolipid metabolism. Notably, tangeretin downregulated four biosynthetic genes (Fum2, Fum3, Fum10 and Fum11) that are involved in the final steps of fumonisin formation. It likely disrupted the MAPK signaling pathway and targeted a putative NmrA- and HSCARG-like protein Fv_Tan1, which was identified as having positive effects on fungal growth and mycotoxin biosynthesis. This study presents a promising approach for controlling fumonisin contamination in agricultural settings.